Maternal ADHD Symptoms, Personality, and Parenting Stress: Differences Between Mothers of Children With ADHD and Mothers of Comparison Children. Issue 13 (November 2018) - Perez Algorta, Guillermo; Kragh, Carolyn A.; Arnold, L. Eugene; Molina, Brooke S. G.; Hinshaw, Stephen P.; Swanson, James M.; Hechtman, Lily; Copley, LaRae M.; Lowe, Matthew; Jensen, Peter S.
Objective: Mothers raising a child with ADHD can experience high parenting stress. We evaluated if mothers' personality traits and own ADHD symptoms could also affect parenting stress.Method: 430 biological mothers from the Multimodal Treatment Study of Children with ADHD (MTA mothers) and 237 of a local normative comparison group (LNCG mothers) were evaluated at baseline. Interactions were tested between mothers' group and maternal personality/ADHD symptoms related to parenting stress.Results: Compared to LNCG, MTA mothers had higher parenting stress, self-reported ADHD, neuroticism, and lower conscientiousness and agreeableness. When personality and ADHD were evaluated together, ADHD symptoms interacted with mothers' group: high maternal ADHD was positively associated with parenting stress for LNCG but not MTA mothers.Conclusion: Personality traits or ADHD characteristics do not appear operative for the high parenting stress of mothers of a child with ADHD. However, high maternal ADHD or low conscientiousness are associated with stress levels similar to raising a child with ADHD.